PENGARUH INTERNAL MIXED AIR-ASSISTED NOZZLE TERHADAP ATOMISASI MINYAK JELANTAH DENGAN CEROBONG PEMANAS - R.B,, Alexander Farell; Ghurri, Ainul; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract Air-assisted nozzle operates on low flow rate with a constant pressured air supply mixed with fuels to produce a spray with certain characteristics, namely fuel atomization, spray length, and its angle. A heating funnel is added in front of the nozzle to give a preheating treatment to the spray that shoot through the funnel in result of a more optimalized atomization. In this research, the experiment used an internal mixed air-assisted nozzle to discover the difference of atomization rate of both fuels, which are biodiesel and waste cooking oil. The result showed the difference of atomization rate on internal mixed air-assisted nozzle test, which is an increase of 2% while using biodiesel in compared to waste cooking oil. Keywords: Preheat treatment, Air-assisted atomizer, Nozzle, Spray characteristic, Atomization